2020
DOI: 10.1186/s13020-020-00388-w
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to assess the effectiveness and safety of acupuncture for overactive bladder: a study in Hong Kong population

Abstract: Background Around 15% of the Hong Kong population was found to suffer from overactive bladder (OAB), but the current available treatments, such as medication, behavioral therapy and physical therapy are unsatisfactory. Previous studies have suggested that acupuncture may have promising effect for OAB, but some limitations on the study design render the evidence questionable. This study aimed to evaluate the effectiveness and safety of acupuncture treatment for patients with OAB in Hong Kong. Methods One hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…According to our previous animal experimental protocol [ 27 ] and related clinical studies [ 28 ], acupuncture needles were affixed to the surface of BL33 and SP6 in the sham EA group, without penetrating into the acupoints in order to avoid nonspecific acupuncture effect. The stimulator is connected to the acupuncture needles, but the power switch is turned off.…”
Section: Methodsmentioning
confidence: 99%
“…According to our previous animal experimental protocol [ 27 ] and related clinical studies [ 28 ], acupuncture needles were affixed to the surface of BL33 and SP6 in the sham EA group, without penetrating into the acupoints in order to avoid nonspecific acupuncture effect. The stimulator is connected to the acupuncture needles, but the power switch is turned off.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 25 studies were conducted in China ( 19 – 28 , 30 – 42 , 44 , 45 ), two in the United Kingdom ( 29 , 43 ), one in the United States ( 16 ), one in Turkey ( 18 ), and one in Hong Kong ( 17 ). The main characteristics of the 30 included studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported acupoints, and the more frequently used acupoints included SP6 (17 studies) ( 16 – 19 , 24 – 29 , 31 , 34 , 35 , 39 , 41 , 43 , 44 ), BL23 (17 studies) ( 17 , 19 , 23 – 25 , 27 – 29 , 31 , 35 , 38 – 42 , 44 , 45 ), BL28 (15 studies) ( 16 , 17 , 23 – 25 , 27 – 29 , 31 , 35 , 38 , 39 , 42 , 44 , 45 ), CV4 (15 studies) ( 16 – 18 , 23 , 25 – 27 , 29 , 31 , 34 , 35 , 39 , 40 , 43 , 44 ), BL32 (15 studies) ( 17 , 19 , 21 , 23 – 25 , 27 , 31 – 33 , 35 , 39 , 41 , 44 , 45 ), and CV3 (11 studies) ( 19 , 23 , 25 , 27 , 29 , 31 , 34 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, some studies found no significant difference in the NGF/creatinine ratio between patients with OAB and the control group (17,18). On the other hand, other studies showed unmeasurable NGF concentrations using various commercially available ELI-SA kits (19)(20)(21). These studies have drawn attention to the importance of using multiple methods to establish optimal procedures for biomarker detection in urine.…”
Section: Introductionmentioning
confidence: 99%